The Influence of the Discovery Learning Model with the TaRL Approach on Student Motivation and Learning Outcomes on the Human Digestive System Material in Class XI of SMA Negeri 2 Tebing Tinggi - Avilla, Mita; Pranoto, Hendro (Perspektif Pendidikan dan Keguruan, 2026)
This study aims to determine the effect of the Discovery Learning model with the TaRL approach on student motivation and learning outcomes in the human digestive system in class XI of SMA Negeri 2 Tebing Tinggi. This type of research is a quasi experiment with a Non Equivalent Control Group design. The population in this study were all students of class XI SMA Negeri 2 Tebing Tinggi consisting of 10 classes. Sampling of the research was done by purposive sampling technique. The samples used were XI-2 as a control class using the Discovery Learning model and class XI-3 as an experimental class using the Discovery Learning model with the TaRL approach. The research instruments used were a questionnaire and a Two-Tier Multiple Choice. Based on the results of the data analysis using t-test with Sig. (2- tailed) 0.000 < 0.05 indicates that the Discovery Learning model with the TaRL approach has an effect on student motivation and learning outcomes.